(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
The side chain methacrylic polymers with different active functional group have been well studies and widely applied in many fields, such as: optoelectronics, nonlinear optics, optical storage materials, biochemicals and medicine. Thus, created these polymers is one of actual problems modern polymer chemistry. The copolymer composition and comonomers units distribution depend on monomer reactivity ratios. Important task during synthesis functional polymers is based on finding the relationship between the composition of copolymers and the composition of the monomer feed in which the monomer-reactivity ratios are the parameters to be determined. This article reports the syntheses of methacrylic monomers and polymers based on them. Kinetics of homopolymerization and copolymerization (1:3) of 8-methacryloxystyrylquinolines with MMA were investigated by dylatometric method. The biggest speed of copolymerization was obtained for monomer with fluorine as substitute, a bit lower for monomer with chlorine as substitute, and the lowest speeds were shown for monomer with bromine as substitute and for 8-methacryloxystyrylquinoline. In general, copolymerizations with M1-4 were carried out to high conversions. The synthesis of homopolymers and copolymers based on 2-(2-phenylethenyl)quinolin-8-yl 2-methylpropil-2-enoate and methylmethacrylate were conducted in 10 % DMF solution with AIBN as radical initiator at 80°C (argon atmosphere). The products of polymerization were characterized by 1 HNMR. Constants of polymerization r1 and r2 were determined with the Fineman-Ross (FR) and calculation methods and were found to be r1= 0.26 (0.255±0.004), r2= 0.55 (0.547±0.014). Values of resonance factor Q and polar factor e were calculated using Alfrey-Price scheme and were found to be Q= 2.37, e= 1.8.